Clinical Case of Tocilizumab Use in a Patient with Systemic Juvenile Idiopathic Arthritis - Y. M. Spivakovskiy; Y. V. Chernenkov; A. Y. Spivakovskaya; O. V. Skupova; E. N. Shulgina (Педиатрическая фармакология)
The article presents a case of using genetically engineered biopharmaceutical tocilizumab in a child with systemic juvenile idiopathic arthritis. On the initial stage, the treatment was characterized by resistance to high doses of glucocorticoids and cytostatic drugs. Successful termination of visceral and articular manifestations of systemic juvenile idiopathic arthritis and normalization of laboratory indicators of disease activity in the setting of use of interleukin 6 receptor blocker were described. We observed stable improvement of the child’s condition during a year-long follow-up in the setting of the selected anti-inflammatory therapy pattern.